Clients protection and rights of bancassurance in context of life insurances - Florek, Irmina (Journal of Finance and Financial Law, 2017)
Cooperation of banking institutions with insurance companies, called bancassurance, along with development has noted a significant problem of improper clients protection in the insurance’s sales system. The article will show the essence of bancassurance, the importance of life insurances, the legal bases for this channel and the protection and rights of clients. The aim of the article is to present and evaluate regulations, currently applying in the polish market, relating to relations with bancassurance customers.